Mortality trend due to chronic kidney disease in Brazil: an ecological study - Ellen de Cassia Dutra Pozzetti Gouvêa; Alex Mussoi Ribeiro; Erika Carvalho de Aquino; Sheila Rizzato Stopa (Ministério da Saúde do Brasil, 2023)
ABSTRACT Objective: To analyze chronic kidney disease mortality in Brazil according to sex, age group and region of residence, from 2009 to 2020. Methods: This was a time series study having deaths as its unit of analysis, based on Mortality Information System data. The mortality rate was standardized using the direct method and the temporal trend was analyzed using the Prais-Winsten method. Results: There was a rising trend in chronic kidney disease mortality, ranging from 2.82, in 2009, to 3.24 in 2020 (average annual increase 1.29%; 95%CI 0.73;1.85), with a greater increase in males (1.14% per year; 95%CI 0.52;1.76), those aged 75 years and over (2.23% per year; 95%CI 1.87; 2.60) and in the Northern Region (3.86% per year; 95%CI 1.86;5.90) and Northeast Region (3.36% per year; 95%CI 2.24;4.50). Conclusion: Chronic kidney disease mortality showed a rising trend in the period, with sociodemographic disparities.